Implementasi Sistem Informasi Akuntansi Payroll pada PT. Cipta Multi Axindo (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This study aims to implement payroll accounting information at PT. Cipta Multi Axindo and this research took place at PT. Cipta Multi Axindo. This research was conducted qualitatively, using interviews, observation, and documentation. The data analysis used is descriptive qualitative analysis, which describes the company's payroll accounting information system. Activities in the system, related functions, documents used, related accounting records, and reports generated are all included in this analysis. Because the payroll system of PT. Cipta Multi Axindo still relies on the manual method, the results of this study indicate that the manual calculation system will encounter problems if they arise.